2021
DOI: 10.1002/jclp.23284
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic differences in emotion regulation: A systematic review

Abstract: Objective: Emotion regulation is a transdiagnostic mechanism with relevance to the etiology, maintenance, and treatment of a wide range of clinically relevant outcomes.This study applied systematic review methods to summarize the existing literature examining racial and ethnic differences in emotion regulation.Methods: We systematically searched four electronic databases (PsycINFO, Embase, MEDLINE, and CINAHL Plus) using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines.Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 97 publications
1
7
0
1
Order By: Relevance
“…Studies on ER have increased rapidly across various patient populations, their caregivers, and contexts (Behrouian et al, 2021; O’Toole et al, 2020; Toohey et al, 2016). Consistent with prior work, we found non-White SDMs reported a greater tendency to use cognitive reappraisal and expressive suppression than White SDMs, and SDM men had a higher tendency to use expressive suppression than SDM women (Goubet & Chrysikou, 2019; Nolen-Hoeksema, 2012; Weiss et al, 2022). However, less is known about the interaction of race and gender in the relationship between ER (cognitive reappraisal and expressive suppression) and psychological distress.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Studies on ER have increased rapidly across various patient populations, their caregivers, and contexts (Behrouian et al, 2021; O’Toole et al, 2020; Toohey et al, 2016). Consistent with prior work, we found non-White SDMs reported a greater tendency to use cognitive reappraisal and expressive suppression than White SDMs, and SDM men had a higher tendency to use expressive suppression than SDM women (Goubet & Chrysikou, 2019; Nolen-Hoeksema, 2012; Weiss et al, 2022). However, less is known about the interaction of race and gender in the relationship between ER (cognitive reappraisal and expressive suppression) and psychological distress.…”
Section: Discussionsupporting
confidence: 89%
“…Emotion regulation (ER) is a fundamental skill that SDMs can use to reduce the severity of their psychological distress. Importantly, ER tendencies and the effects of discrete ER strategies differ by racial and gender identity (Nolen-Hoeksema, 2012; Perchtold et al, 2019; Soto et al, 2011, 2012; Webb et al, 2012; Weiss et al, 2022). Yet, in the context of surrogate decision-making in the intensive care unit (ICU), little is known about the ER tendencies that vary between SDMs of different races or gender, and how these differences modify ER’s influence on psychological distress.…”
mentioning
confidence: 99%
“…Culturally relevant strategies for regulating emotions may influence the impact of social stressors on health and well-being (Appleton et al, 2014;Brownlow, 2022;Das, 2013;Thayer et al, 2020). Recent work suggests that social and cultural factors, including race, impact the usage of emotion regulation strategies (Weiss et al, 2022). In particular, Black Americans appear to engage in expressive suppression more often than White Americans (Wilson & Gentzler, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In US samples, the use of expressive suppression is higher among ethnoracial minorities, suggesting that ethnoracial minorities may be more motivated to downregulate emotional expression (for a review, see Ref. (13)). A recent review found that African Americans frequently use expressive suppression as a coping mechanism in response to racial discrimination (14), and research suggests that suppression may in fact be health protective in this context, specifically for African American women (15).…”
Section: Introductionmentioning
confidence: 99%